2019
DOI: 10.3389/fnins.2019.00262
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiology of Avian Sleep: Comparing Natural Sleep and Isoflurane Anesthesia

Abstract: Propagating slow-waves in electroencephalogram (EEG) or local field potential (LFP) recordings occur during non-rapid eye-movement (NREM) sleep in both mammals and birds. Moreover, in both, input from the thalamus is thought to contribute to the genesis of NREM sleep slow-waves. Interestingly, the general features of slow-waves are also found under isoflurane anesthesia. However, it is unclear to what extent these slow-waves reflect the same processes as those giving rise to NREM sleep slow-waves. Similar slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
1
11
0
1
Order By: Relevance
“…finches. Similar events have also been described in anesthetized pigeons (24). This evidence for avian SWRs follows similar evidence in sleeping reptiles (13,14) and suggests that the evolutionary origin of large-amplitude, highly synchronous SWR events may have already been present in the stem-amniote ancestor to birds, reptiles, and mammals.…”
Section: Discussionsupporting
confidence: 81%
“…finches. Similar events have also been described in anesthetized pigeons (24). This evidence for avian SWRs follows similar evidence in sleeping reptiles (13,14) and suggests that the evolutionary origin of large-amplitude, highly synchronous SWR events may have already been present in the stem-amniote ancestor to birds, reptiles, and mammals.…”
Section: Discussionsupporting
confidence: 81%
“…The mechanisms that mediate avian slow wave propagation remain unclear. Nonetheless, from multi-electrode recordings of anesthesia-induced slow waves, which in many aspects, including propagation pattern, resemble NREM slow waves (van der Meij et al, 2019b), it is clear that the extracellular depolarization of LFP waves is spatio-temporally closely matched by local action potential activity (Beckers et al, 2014), as is the case during NREM sleep in the human neocortex (Nir et al, 2011). Consequently, propagating slow waves appear to reflect the sequential local activation of neurons in the avian brain.…”
Section: Local Aspects Of Nrem Sleepmentioning
confidence: 99%
“…Nonetheless, the precise mechanisms by which the general anesthetics cause the sudden reversible loss of consciousness, remain to be pinpointed. The sedative effects of anesthetics such as drowsiness, calmness and reduction of motor tone are behaviorally similar to the features of the non-rapid eye movement (NREM) period of sleep ( Franks and Zecharia, 2011 ; van der Meij et al, 2019 ). Some whole-brain imaging studies have also shown that the states of “unconsciousness” during deep sleep and anesthesia are remarkably similar ( Franks, 2008 ).…”
Section: Introductionmentioning
confidence: 97%
“…Some whole-brain imaging studies have also shown that the states of “unconsciousness” during deep sleep and anesthesia are remarkably similar ( Franks, 2008 ). Moreover, similar slow-wave spatiotemporal properties during NREM sleep and isoflurane anesthesia suggest that both types of slow-waves are based on related processes ( van der Meij et al, 2019 ). Recently, growing evidence proved that general anesthesia-induced unconsciousness and natural sleep shared some neural networks ( Zhong et al, 2017 ; van der Meij et al, 2019 ; Zhang et al, 2019 ; Liu et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%